Analisis Tingkat Kecepatan Korosi Besi dengan Menggunakan Sinar Gamma - Lubis, Ashar Muda; Supiyati, Supiyati (Jurnal Fisika FLUX, 2009)
In order to examinate rate of iron corrosion, we have conducted aresearch using apparatus Geiger-Muller Tube with sources radiation standardCo-60 as a source of Gamma ray. The samples, iron plate with diameter 2 cmand thichness 0.13 cm, were corroded by various media of corrosion i.e. water(H2O), solution of salt (NaCl) and sulphuric acid (H2SO4) with interval timecorrosion Â± 5 days, 10 days, 15 days, 20 days, and 25 days. Firstly, weestimated intensity of Gamma ray before (Io) and after (I) passing through thesamples, and then we evaluated the absorption coefficient of samples. Weobtained that equation of absorption coefficient is A (water) = 0.0014t â 0.4608;R2 = 0.9184, A (salt solution) = 0.0015t â 0.4589; R2 = 0.8886 and A (sulphuricacid) = 0.0017t â 0.4532; R2 = 0.780. We calculated that the rate of corrosion forwater, salt solution and sulphuric acid is 0.0014 gr/cm2/day, 0.0015 gr/cm2/dayand 0.0017 gr/cm2/day respectively. The result shows the rate of corrosioncaused by sulphuric acid larger than corroded by salt and water. In addition, therates of corrosion of iron depend on interval time of corroding iron plate andmedia of corrosion. Another factor which may be related to rate of iron corrosionsuch as temperature, humidity and concentration of media of corrosion should beconsidered for next future.